Two new records of the coral symbiont crab genus Quadrella Dana, 1851, from Taiwan, with notes on the taxonomy of Q. boopsis Alcock, 1898 (Crustacea: Brachyura: Trapeziidae) - Lin, Chia-Wei; Ng, Peter K. L. (Zootaxa, 2017)
Two symbiotic trapeziid crabs of the genus Qudrella Dana, 1851, were collected from southwestern Taiwan. Both are new records for the island. Quadrella coronata Dana, 1852, is usually associated with the soft coral Chironephthya spp., while Q. boopsis Alcock, 1898, was found with the scleractinian coral Tubastraea micrantha. The taxonomy of Q. boopsis is treated and the variation in the dorsal surface of the carapace, armature of the anterolateral margin and colour pattern discussed.